Boron–nitrogen substituted dihydroindeno[1, 2-b]fluorene derivatives as acceptors in organic solar cells. Issue 74 (28th August 2019) - Morgan, Matthew M.; Nazari, Maryam; Pickl, Thomas; Rautiainen, J. Mikko; Tuononen, Heikki M.; Piers, Warren E.; Welch, Gregory C.; Gelfand, Benjamin S.
Abstract : Derivatives of a new non-fullerene acceptor core based on a BN substituted indenofluorene framework show 2% PCE in organic solar cells. Abstract : The electrophilic borylation of 2, 5-diarylpyrazines results in the formation of boron–nitrogen doped dihydroindeno[1, 2- b ]fluorene which can be synthesized using standard Schlenk techniques and worked up and handled readily under atmospheric conditions. Through transmetallation via diarylzinc reagents a series of derivatives were synthesized which show broad visible to near-IR light absorption profiles that highlight the versatility of this BN substituted core for use in optoelectronic devices. The synthesis is efficient, scalable and allows for tuning through changes in substituents on the planar heterocyclic core and at boron. Exploratory evaluation in organic solar cell devices as non-fullerene acceptors gave power conversion efficiencies of 2%.